Pendidik Islam dalam Kajian Surat Ali Imron Ayat 164 - Ulum, Miftachul; Mun'im, Abdul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this research is to describe the role and duties of educators from the perspective of Surah Al-Imran, verse 164. The research method is library research. This research focuses on the study of Surah Al-Imran verse 164. The researcher conducted an analysis of the content of the verse and presented a detailed description. The research findings indicate that educators must be able to play the roles of a teacher (muallim), instructor (mudarris), guide (murabbi), disciplinarian (muaddib), and mentor (mursyid). for the students